Incongruence Between Learning Style and Written Corrective Feedback Type: Mediating Effect of Implicit Theory of Learning Style - Jalali, Hanan; Rahimi, Mohammad (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2022)
Implicit theory (Dweck, 2000) suggests that learners’ theories about the malleability of their individual traits (learning style, here) determine the extent to which they can stretch their learning style (Gregersen & MacIntyre, 2014; Young, 2010) and benefit from the instruction that mismatches their preferred styles. The present study aimed at investigating the extent to which Iranian EFL learners with inductive vs. deductive learning styles would benefit from the written corrective feedback (WCF) that does not match their learning styles (i.e., implicit vs. explicit WCF). The study also examined if their success (or lack of) in style stretching and improving their written accuracy is due to the implicit theory (entity vs. incremental) they hold about their learning style. The result showed that students with an incremental theory significantly improved their written accuracy more than those with an entity theory. Also, the findings revealed that inductive learners were more successful in adapting to the mismatched WCF (explicit) and made greater improvement in their written accuracy than deductive students who received implicit WCF.